Застосування методу малого параметру при моделюванні задач теорії в҆язкопружності - Кагадій, Тетяна Станіславівна; Kagadiy, Tatiyana; Білова, Оксана Вікторівна; Belova, Oksana; Щербина, Ірина Володимрівна; Shcerbyna, Irina (Херсонський національний технічний університет, 2019)
При побудові моделей складних задач теорії пружності і в'язкопружності доводиться вдаватися до спрощення дозвільних систем рівнянь. Одним з ефективних підходів є методи малих параметрів. У даній роботі описаний метод збурень коли малий параметр являє собою відношення характеристик жорсткості. Початкові ідеї методу викладені в [2]. У даній роботі метод узагальнено на випадок просторових задач лінійної теорії в'язкопружності. Вдалося не просто розщепити напружено-деформований стан на три складові з різними властивостями, але і зберегти зв'язок між цими станами, що підвищує якість математичної моделі і наближає її до реальної задачі. Для демонстрації ефективності роботи даного методу наведено розвʼязання модельної задачі для в'язкопружного ортотропного тіла з циліндричною анізотропією. At construction of models of challenges of the theory of an elasticity and viscoelasticity is necessary to resort to simplification of resolving set of equationses. One of effective approaches is method of small parameters [1]. In the given work the method of perturbations is described when the small parameter represents the ration stiff performances. Initial ideas of a method are stated in [2]. In the given work the method is generalized on a case of spatial problems of the linear theory viscoelasticity. It was possible to split not simply the intense-deformed condition on three components with various properties, but also to keep connection between these conditions that raise quality of mathematical model and approximates it to a real problem. For demonstrating an overall performance of the given method the solution of a modelling problem for a viscoelastic orthotropic skew field with cylindrical anisotropy is reduced. At mathematical modelling the intense-deformed condition of viscoelastic skew fields with switch connections or battening plates it is possible to use various methods, both analytical, and numerical (for example, a finite element method). To shortages of numerical methods it is possible to refer complexities in view of strong anisotropy of a material. At a solution of a problem an asymptotic method applied by authors nuances of a select of small parameter give a boomerang effect. The more strongly anisotropy of a material, the more precisely received solutions. Earlier the given method has been applied to a solution of contact problems about a load transmission from elastic switch connections to elastic plates with curvilinear anisotropy. The analysis of the differential equations of the spatial theory viscoelasticity an orthotropic skew field is lead. The intense-deformed condition of such skew field is split on three components with various properties which are connected through boundary conditions on shearing stresses. The solution of an initial problem is in the form of superposition of components. The possibility of a statement of boundary conditions for searching trial functions that reduces a solution of a spatial problem of the theory viscoelasticity to sequentially solved boundary value problems of a potential theory is shown. As the received solutions represent transforms of Laplace the method of returning to pre-images by means of two-point approximant Pade and limit representations of required magnitudes is offered. Effectiveness of such approach is shown on a modelling problem.
Application of a method of small parameter at modelling problems of the theory viscoelasticity
Keywords: асимптотичний метод; аsymptotic method; ортотропний матеріал; orthotropic material; в´язкопружність; viscoelasticity; циліндрична анізотропія; cylindrical anisotropy; модельна задача; modelling problem